Comparative analysis of WiMAX decoders using VHDL - Sharma, Kanchan (My University, 2015)
Decoders are multiple input-multiple output models. Viterbi decoder is used in applications of wireless communication where convolutional codes are required to be decoded. The working of this is as per design as well as implementation of convolutional encoder along with Viterbi decoder.
Master of Engineering (Electronics and Communication)
Keywords: WiMAX; LDPC; Turbo decoder; Viterbi decoder; electronics and communication; electronics